Land Registration for the Community in the Kampung Tua Area, Batam City - Andini, Maysha; Warman, Kurnia; Andora, Hengki (Journal of Law, Politic and Humanities, 2025)
The problem of land registration in the Kampung Tua area of Batam City reflects the complex dynamics between the historical recognition of local communities and the formal agrarian legal system that applies in Indonesia. Until now, most of the land in Kampung Tua does not have a land rights certificate, even though it has been controlled by the community for generations. The dualism of authority between the Batam City Government and the Batam Business Agency (BP), as well as the insynchronization of regulations and spatial data, are the main obstacles in the process of legalizing people's rights. This research aims to analyze the land registration process in Kampung Tua, identify the types of rights granted to the community, and uncover obstacles and formulate strategic solutions in the context of local land policies. The method used is juridical-empirical, with a descriptive qualitative approach through document studies and in-depth interviews with relevant agencies, such as BPN, BP Batam, City Government, and community leaders. The results of the study show that the clarity of the legal status of land in Kampung Tua is very urgent to provide protection of community rights and encourage agrarian justice. It is necessary to strengthen single authority, prepare contextual technical regulations, and socialize legal procedures to the public in a more participatory manner.